Reimbursement Based on Value in Knee Surgery: What You Need to Know about the Medicare Access and Children's Health Insurance Program Reauthorization Act of 2015 - Saleh, Khaled J.; Sayeed, Zain; Anoushiravani, Afshin A.; Darwiche, Hussein F.; Little, Bryan; Frush, Todd James; El-Othmani, Mouhanad M. (The Journal of Knee Surgery, 2017)
Health care cost is consuming a large portion of the nation's gross domestic product while placing added economic burdens on physicians and their patients. With total joint replacement being one of the early-targeted procedures in the evolving health care environment, knee surgeons will benefit from developing a critical knowledge on health care reforms and their financial implications. The Medicare Access and Children's Health Insurance Program Reauthorization Act represents a cohesive movement toward value-based payment reform and contains several unchartered rulings that require detailed attention by knee surgeons. In this article, we provide a contextual framework of health care legislation that has led to the formation of the current health policy, and present a comprehensive summary and update on the Merit-Based Incentive Payment Systems and Alternative Payment Models reimbursement models.
Keywords: health care reform; reimbursement models; MACRA; MIPS; APM